The Ubiquitin Ligases c-Cbl and Cbl-b Negatively Regulate Platelet-derived Growth Factor (PDGF) BB-induced Chemotaxis by Affecting PDGF Receptor β (PDGFRβ) Internalization and Signaling - Rorsman, Charlotte (J Biol Chem, 2016)
Protein ubiquitination controls protein stability and subcellular localization of tyrosine kinase receptors, hence affecting signaling both quantitatively and qualitatively. In this report, we demonstrate that, after ligand stimulation, the PDGF β receptor (PDGFRβ) becomes ubiquitinated in a manner requiring both the c-Cbl and Cbl-b ubiquitin ligases. Simultaneous depletion of c-Cbl and Cbl-b resulted in reduced ligand-induced PDGFRβ clearance from the cell surface because of reduced endocytosis of the receptor. Cbl-b formed a complex with c-Cbl, as well as with the PDGFRβ, in response to PDGF-BB stimulation. We were unable to find a direct interaction between the receptor and c-Cbl, raising the possibility that Cbl-b is necessary for c-Cbl to interact with PDGFRβ. Phosphorylated Tyr-1021 in PDGFRβ was the primary interaction site for Cbl-b, with some contribution from Tyr-1009. Depletion of c-Cbl and Cbl-b led to an increased ligand-induced tyrosine phosphorylation of the receptor. Several tyrosine residues with elevated phosphorylation (i.e. Tyr-579, Tyr-581, Tyr-1009, and Tyr-1021) have previously been shown to interact with Src kinases and PLCγ. Indeed, in cells depleted of c-Cbl and Cbl-b, both Src and PLCγ phosphorylation were enhanced, whereas activation of other pathways, such as Erk1/2 MAP kinase and Akt, were not affected. In addition, Stat3 phosphorylation, which has been connected to Src activity, was also elevated in cells lacking c-Cbl and Cbl-b. Functionally, we found that cells depleted of c-Cbl and Cbl-b were more prone to migrate toward PDGF-BB, whereas no reproducible effect on cell proliferation could be observed. In conclusion, internalization as well as signaling via PDGFRβ are controlled by ubiquitination.